2005
DOI: 10.1007/s11165-004-3437-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Studies: Designs, Validity, Practicality, and Value

Abstract: Aiming to encourage longitudinal studies in science education, we clarify conceptual and methodological aspects of longitudinal research. We use the studies that other articles in this issue describe to illustrate these aspects. The illustrations range from attempts to promote long-term change through experimental teaching to investigations that describe change without intending to affect it. For both experimental and descriptive studies we discuss the validity of conclusions and insights, and how threats to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 2 publications
(4 reference statements)
1
56
0
7
Order By: Relevance
“…In the study we have accomplished interviews and interventions shown in Table 1. Table 1, please insert about here White and Arzi (2005) make a distinction between studies that are experimental, leading to conclusions and those that are descriptive leading to insights. We would describe our study as descriptive, hopefully, leading to new insights.…”
Section: Design and Samplementioning
confidence: 99%
“…In the study we have accomplished interviews and interventions shown in Table 1. Table 1, please insert about here White and Arzi (2005) make a distinction between studies that are experimental, leading to conclusions and those that are descriptive leading to insights. We would describe our study as descriptive, hopefully, leading to new insights.…”
Section: Design and Samplementioning
confidence: 99%
“…As no study tracked changes in individuals throughout their retirement processes, the studies were unable to detect shifts or developments in the characteristics of subjects at the group or individual level [58]. However, as retirement is a process that may span decades, surveys that only query retirees at a single point in time lack the ability to fully contribute to our understanding of physicians' adjustment to retirement.…”
Section: Batchelor (1990)mentioning
confidence: 99%
“…We follow White and Arzi's (2005) definition of longitudinal design: "A longitudinal study is one in which two or more measures or observations of a comparable form are made of the same individuals or entities over a period of at least one year" (p. 138). In longitudinal research, Bauer (2004) differentiates between "cohort" and "panel" studies.…”
Section: Characteristics Of Longitudinal Researchmentioning
confidence: 99%
“…However, longitudinal designs have their own special problems (e.g., time, resources, data management, attrition, and cost) and are often difficult to implement (White & Arzi, 2005). By their very nature they extend over a period of time with data being gathered throughout this period.…”
Section: Characteristics Of Longitudinal Researchmentioning
confidence: 99%